2018
DOI: 10.1108/ebr-12-2016-0161
|View full text |Cite
|
Sign up to set email alerts
|

Engaged in integrated reporting? Evidence across multiple organizations

Abstract: Purpose The purpose of this paper is twofold: to provide evidence on geographic and firm-level characteristics within organizations using integrated reporting (<IR>) methodology to communicate their business model to stakeholders; and to shed light on the contend of integrated reports of organizations that have been recognized as leading practice by a reputable award process or through benchmarking. Design/methodology/approach Secondary analysis of data (descriptive and inferential statistics) is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
1
16
1
3
Order By: Relevance
“…Often times, it has been argued that companies are influenced by their customers and their sensitivity to CSR and CSR reporting [51]. Similarly, in a recent research study on integrated reporting, it was found that the majority of integrated reporters are from Europe [52]. In South Africa, perhaps also due to the requirement for IR at the JSE, it was found that companies are more likely to produce an integrated report than in other countries [33,38,43].…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Often times, it has been argued that companies are influenced by their customers and their sensitivity to CSR and CSR reporting [51]. Similarly, in a recent research study on integrated reporting, it was found that the majority of integrated reporters are from Europe [52]. In South Africa, perhaps also due to the requirement for IR at the JSE, it was found that companies are more likely to produce an integrated report than in other countries [33,38,43].…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Signaling theory suggests that more profitable companies will voluntarily publish information to distinguish themselves from less profitable organizations. Various research studies that examine the relationship between profitability and voluntary disclosure found that more profitable companies disclose better quality information [25,52,58]. For instance, it was found that profitability was positively and significantly associated with voluntary disclosure levels for Kenyan financial institutions [36].…”
Section: H1mentioning
confidence: 99%
“…Companies in need of external funding will arguably be more likely to disclose information than those with sufficient internal funds (Dilling & Caykoylu 2019). Lopes and Coelho (2018) suggested that companies with a high level of IRQ tend to be large, profitable and less leveraged.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The categorised EY Excellence in Integrated Reporting Awards was used to assess the companies' IRQ. The usage of these rankings enabled the authors to consider so-called 'reference reporters', namely those that received recognition through an award scheme (Lopes & Coelho 2018). Accounting and market-based financial and sustainability data -environmental, social and corporate governance (ESG) scores -were sourced from Bloomberg (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Este fenómeno tiene variados sustentos conceptuales, tales como la teoría de la legitimidad(Ashforth & Gibbs, 1990), teoría institucional(Farooq & Maroun, 2018), teoría de agencia(Villiers & Hsiao, 2018) y teoría de los stakeholders(Fernández & Sanjuan, 2012).En este escenario y dada la abundancia de información y múltiples reportes, se hace difícil establecer una imagen global de la compañía(Jensen & Berg, 2012;Rivera, Zorio, & García, 2017).En función de esto, el Reporte Integrado tiene por objetivo mostrar en tan solo un documento la potencialidad de la empresa para crear valor en el corto y largo plazo, a través de una visión holística de la entidad(Lizcano, Flores, & Rejón, 2015;IIRC, 2013;Fernández & Ramón, 2013;Rivera, Zorio, & García, 2016), y se ha transformado en una innovadora herramienta para informar aspectos esenciales y útiles para las partes interesadas(Hauque & Rabasedas, 2014). A pesar de que la mayor parte de las empresas que emiten el reporte son europeas(Lopes & Coelho, 2018), esta tendencia también llegó a Chile, donde ya existe un reducido número de empresas que, voluntariamente han decidido emitir este reporte.En ese contexto, el análisis de la adopción temprana del Reporte Integrado en Chile se presenta como un problema de investigación relevante. Dado lo anterior, este trabajo tiene como objeti-…”
unclassified